Important Green Chemistry and Catalysis: Non‐phosgene Syntheses of Isocyanates – Thermal Cracking Way. Issue 6 (8th May 2017) - Wang, Peixue; Liu, Shimin; Deng, Youquan
Abstract : Currently, industrial production of isocyanates, or diisocyanates in particular, has been exclusively based on phosgene processes. Phosgene is extremely toxic and large amounts of corrosive HCl are produced as a side product. In the view of environment protection and society safety, development of non‐phosgene processes for isocyanates production will be highly desired, and this should be one of the most important missions for green chemistry and catalysis. In this review, efforts for development of non‐phosgene method for syntheses of isocyanates, i.e., catalytic syntheses of N‐substituted carbamates from nitro‐ or amino‐compounds with CO, dimethyl carbonate (DMC), urea and even CO2 etc. as carbonyl sources, then thermal cracking of N‐substituted carbamates to afford corresponding isocyanates, are summarized, and a brief prospect for non‐phosgene syntheses of isocyanates is also addressed. Abstract : Efforts for development of non‐phosgene method for syntheses of isocyanates, i.e., catalytic syntheses of N‐substituted carbamates from nitro‐ or amino‐compounds with CO, dimethyl carbonate (DMC), urea and even CO2 etc. as carbonyl sources, then thermal cracking of N‐substituted carbamates to afford corresponding isocyanates, are summarized, and a brief prospect for non‐phosgene syntheses of isocyanates is also addressed.